The Relationship Between Age and Anxiety Levels of Emergency Room Nurses in The Covid-19 Era - Dwi Antara Nugraha; Harul Harisman; Matius Benu Supargianto (Jurnal Indonesia Sehat, 2022)
Background: This study aims to determine the relationship between age and anxiety levels of nurses working in the Emergency Installation during the Covid-19 pandemic era at the Yogyakarta Special Region Private Hospital. Methods: This research is a correlational non-experimental quantitative retrospective study with a cross-sectional approach that aims to find answers to the correlative relationship between variables and observations of events that have occurred. The research population is nurses who work in the Emergency Installation of Private Hospitals in Yogyakarta. The sampling technique used in this research is purposive sampling. Statistical test analysis using Spearman's test. Result: The relationship between the two variables is unrelated or uncorrelated with the value of Sig. (2-tailed) 0.183, the correlation strength level is very weak and the direction of the relationship is negative with the Correlation Coefficient of -0.174. Conclusion: The results of the statistical test show that there is no relationship or correlation between age and the anxiety level of nurses working in the emergency room of a private hospital in the Special Region of Yogyakarta during the Covid 19 pandemic.